Penentuan Penerimaan Mahasiswa Terhadap Aplikasi Menghitung Invers Matrik Ordo 3x3 Dan 4x4 Dengan Pendekatan User Acceptance Test - Efy Yosrita; Rakhmat Arianto (Sekolah Tinggi Teknik - PLN, 2017)
Simulation application calculate the inverse order of 3x3 and 4x4 matrices developed to help students understand the process of finding the inverse of a matrix. To find out how the rate of admissions to the simulation application calculate the inverse matrix of order 3x3 and 4x4 tested using the method of User Acceptance Test. In this test data taken are students who have used the application. Based on the experiments, we concluded simulation application calculate the inverse matrix can be used as a medium of learning for students